Wheat germ agglutinin-positive cells in a stem cell-enriched fraction of mouse bone marrow have potent natural suppressor activity. - Sugiura, K (1988)
In the present study we have characterized natural suppressor (NS) cells, which nonspecifically suppress mitogen responses and mixed-lymphocyte reaction. The strongest NS activity was found in a fraction of relatively low-density cells (1.063 less than p less than 1.075) obtained by equilibrium density centrifugation. Further purification and characterization of these NS cells by using a fluorescence-activated cell sorter indicated that wheat germ agglutinin (WGA)-positive cells have potent NS activity, whereas WGA-negative cells have no NS activity. Spleen colony-forming unit (CFU-S) assays demonstrated a significant correlation between the number of CFU-S cells and the NS activity in the bone marrow. However, WGA-positive cells obtained from the bone marrow of animals treated with 5-fluorouracil, which cells in turn were exposed to 5-fluorouracil, showed a marked reduction in NS activity. These results suggest that the pluripotent stem cells have NS activity when the cells are in the cycling phase but not when the cells are in the G0 phase. It seems possible that apparently primitive cells play an important role in down-regulation of immune responses.